Concentration of Major Elements, Trace Elements, and Heavy Metals and Risk Assessment of Water Quality for Consumption and Agriculture at Nong Leng Sai Reservoir, Mae Jai District, Phayao Province - นทีวัฒนา, จอมจันทร์; สุทธจิตต์, ไมตรี; เทียนถาวร, วิชัย; คิม, แซง ดอน; คิม, ควอง วู (KKU Science Journal, 2015)
Nong leng Sai is the vital freshwater marsh of Phayao province for consumption, agriculture, and human well being. This water source conservation within needs of Mae Jai district residents is necessary. The objectives of study were to risk assessment of physicochemical properties, concentrations of major and trace elements, heavy metals for surveillance water quality to consumption and irrigation, as well as to assess health risk from drinking water. The result showed that physico-chemical characteristics included pH, dissolved oxygen (DO), electrical conductivity (EC), hardness, and total dissolved solid (TDS) were under the permissible limit. As a result of element concentrations, Fe concentration ranged from 312.44–563.52 µg∙L-1 exceed drinking water guideline and high risk. In the addition the concentrations of Al, Mn, Pb, and Se were indicated medium risk. Health risk indicators as follow health risk index (HRI) and hazard index (HI) revealed that non-carcinogen effects of single elements and overall elements were posed insignificant health risk (HRI and HI<1.0). Cancer risk stayed at the highest safe standard for carcinogenic risk. Therefore this water source appropriated quality for consumption after pre-treatment for Fe elimination for example aeration and filtration, reverse osmosis. On the other hands, the risk assessment of water quality for agriculture exposed that the physicochemical parameters were within allowable Food and Agriculture Organization of the United Nations (FAO) standard. Elevated concentration of potassium was above FAO standard at 1.84 mg∙L-1. Nevertheless local community should participate to surveillance water quality of Nong Leng Sai for sustainable utilization.